Epstein–Barr virus‐positive mucocutaneous ulcer: A unique case occurring in association with cholelithiasis in a gallbladder. Issue 1 (9th October 2020) - Awadh, Mohmmed; O'Mahony, John; Ryan, Ciara; Quinn, Fiona; Bacon, Larry; Ravi, Narayanasamy; Flavin, Richard
Abstract : Epstein–Barr virus (EBV)‐positive mucocutaneous ulcer is a lymphoproliferative disorder occurring in patients due to iatrogenic or age‐related immunosuppression confined to the oropharynx, skin, and gastrointestinal tract. Here, we report the first case to our knowledge of EBV‐positive mucocutaneous ulcer occurring in a gallbladder.